2008
DOI: 10.1007/s12031-008-9156-5
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relation of Hemin-Induced HO-1 Expression to the Upregulation of VEGF and BDNF mRNA Levels in Rat C6 Glioma Cells

Abstract: Glial cells are generally considered to contribute to retaining the integrity of neural function through the protection of neuronal cells against neurodegenerative insults and also expected to play a potential role in the protection of cerebrovascular systems from various toxic insults of hemorrhaged blood, thus proposing a possible implication of glial cells in the recovery of brain function from the damage caused by cerebral hemorrhage. Based on this hypothetical idea, the direct effect of hemin on the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 62 publications
3
9
0
Order By: Relevance
“…Activation of Nrf2 stimulates transcription of ATF4, which in turn directly transactivates the VEGF gene in endothelial cells (Afonyushkin et al, 2010, 2011). In addition, HO-1, whose expression level was regulated by Nrf2 in the present study, mediates the synthesis of VEGF in various cell types (Dulak et al, 2008), as well as BDNF and GDNF in astrocytes and neurons (Morita et al, 2009; Hung et al, 2010). These studies suggest that minocycline-induced overexpression of Nrf2 and subsequent up-regulation of HO-1 lead to increased paracrine factor expression.…”
Section: Discussionsupporting
confidence: 49%
“…Activation of Nrf2 stimulates transcription of ATF4, which in turn directly transactivates the VEGF gene in endothelial cells (Afonyushkin et al, 2010, 2011). In addition, HO-1, whose expression level was regulated by Nrf2 in the present study, mediates the synthesis of VEGF in various cell types (Dulak et al, 2008), as well as BDNF and GDNF in astrocytes and neurons (Morita et al, 2009; Hung et al, 2010). These studies suggest that minocycline-induced overexpression of Nrf2 and subsequent up-regulation of HO-1 lead to increased paracrine factor expression.…”
Section: Discussionsupporting
confidence: 49%
“…In this sense, the need for studying the prognostic significance of HO-1 in colon cancer is urgent. Results of several studies have indicated that neurotrophic factor-enhanced HO-1 expression promotes cancer cell proliferation (Morita et al 2009). In our previous study and the present report, we investigated the molecular mechanism of HO-1 and its role in cancer cell motility .…”
Section: Discussionmentioning
confidence: 99%
“…Candidate proteins were selected based on prior studies on brain injury, or BBB disruption that suggested that these markers are brain specific, and based on availability of the respective assays for detection in our laboratory (10, 24, 30, 46, 47, 55). The goal of this study was to determine whether there are differences in plasma concentrations of these markers between patients with malignant gliomas and those without and to assess whether our findings would warrant further investigation of these markers as potential biomarkers for gliomas.…”
Section: Introductionmentioning
confidence: 99%